Navigating the Diagnostic Dilemma of Hodgkin Lymphoma in Adolescents: A Primary Care Perspective - Rashid, Aneesa Abdul; Ain Mohd Noor, Noor Faridzatul (International Journal of Human and Health Sciences (IJHHS), 2024)
Hodgkin lymphoma (HL) is a type of lymphoma that accounts for around 7% of childhood cancers,most common in adolescents aged 15 to 19.(1) This case report describes the clinical presentation,diagnosis, and management of a 17-year-old male diagnosed with HL, highlighting the impact onhis education, peer relationships, and the psychosocial challenges faced by his family. The caseemphasizes the importance of early detection, effective management strategies, and the role ofprimary care in ensuring comprehensive care and support for patients with HL. Challenges relatedto teleconsultation and the importance of psychosocial support are also discussed. International Journal of Human and Health Sciences Vol. 08 No. 04 Oct’24 Page: 368-371